Poor mental health and uptake of disability benefits - O’Reilly, Dermot; Rosato, Michael; Wright, David; Tseliou, Foteini; Miller, Ana Corina; Maguire, Aideen (International Journal of Population Data Science, 2019)
Background with rationale Disability related social security benefits were introduced to help off-set the additional costs incurred by people with disability and to help them better integrate into society. However, there are concerns that not everyone with a disability is receiving the benefits to which they are entitled. Aim To undertake a record-linkage study to compare levels of benefit uptake Disability Living Allowance (DLA) according to disability type and severity as reported in the Northern Ireland 2011 Census. Data/methods The linked data sources were the 2011 census records and all DLA records for calendar year 2011. The main comparison was of DLA receipt amongst those reporting chronic mobility difficulties (MD) and those with chronic poor mental health (PMH) (both yes/no) with the addition of limitation of daily activities (none, a little, a lot), which was used as a proxy for severity and DLA eligibility. Results Most people with disability had multiple disabilities but here the analysis is primarily amongst people with solitary conditions to avoid potential confounding. Approximately 20,000 people in the population reported either only MD or only PMH, though 68% of MD had their daily activities limited a lot compared to 55% of those with PMH. Overall, 71.8% of people with MD and daily activities limited a lot were on DLA compared to only 57.5% of similarly affected people with PMH the relative odds ratio being (OR 0.53 95%CI 0.50, 0.56). Conclusion It appears that people with poor mental health are less likely to receive disability benefits compared to those with mobility problems. This may be because they are less able to prove their eligibility for these benefits under the current assessment processes.